Comparison of Naturally Conceived and IVF-DZ Twins in the Netherlands Twin Registry: A Developmental Study - Catharina E. M. van Beijsterveldt; Meike Bartels; Dorret I. Boomsma (Hindawi Limited, 2011)
In a large set of twin pairs, we compared twins born after IVF to naturally conceived twins with respect to birth characteristics, growth, attainment of motor milestones, and emotional and behavioral problems. Twin families were registered with the Netherlands Twin Register. We included 1534 dizygotic (DZ) twins born after IVF, 5315 naturally conceived (NC) DZ twins, and 1504 control NC DZ twins who were matched to the IVF twins based on maternal age, maternal educational level, smoking during pregnancy, gestational age, and offspring sex. Data were obtained by longitudinal surveys sent to fathers, mothers, and teachers at ages 1, 2, 3, 7, 10, and 12 years. Results showed no differences in growth, in attainment of motor milestones, and in behavioral development between IVF and matched NC twins. It can be concluded that for nearly all aspects, development in IVF and NC children is similar.